Subacute bacterial endocarditis secondary to mastoiditis: a rare complication. (30th November 2012) - Smith, Caroline Patricia; Jackson, Conor; Stewart, Rosemary
Abstract : Mastoiditis can result from untreated otitis media. If unrecognised, it can result in life-threatening complications. We present a 69-year-old woman with a history of left-sided otitis media admitted to intensive care unit following collapse with a decreasing Glasgow Coma Scale. Myringotomy and ventilator insertion revealed pus in the middle ear, which grew Group A Streptococcus . Her fever persisted and blood samples cultured Group A Streptococcus . Echocardiogram confirmed subacute bacterial endocarditis. Subacute bacterial endocarditis is a rare complication of mastoiditis. A literature review detected no previous case reports. A high suspicion of potential complications can prevent morbidity and mortality.